НАЦИОНАЛЬНЫЕ ОСНОВЫ В ЭПОСЕ «БАХАДЫР» ПОЭТА А.ДАБЫЛОВА - Алланазаров, Е. (SCIENCE and SOCIETY, 2025)
The article discusses the reflection of folklore traditions and new realistic aspects in the epic poem "Bahadyr" by the people's poet A. Dabylov. In particular, the work's deep philosophical and patriotic aspects, especially the friendship of peoples, and its connection with reality are comprehensively scientifically analyzed.
Keywords: national epic traditions of folklore; folklore; landscape poetry (Nature Poetry) composition